Co-Assembled Nanoparticles Comprising Sorafenib and Hederagenin Derivative for Enhanced Anti-Hepatic Fibrosis Activity - Lu M; Dai Z; Lin Y; Sun C; Li S; Guo Z; Liu Y; Liu X; Li S; Liu R; Xu B; Lei H (International Journal of Nanomedicine)
Mingjun Lu,* Ziqi Dai,* Yixuan Lin, Changsheng Sun, Shuo Li, Zhuoqian Guo, Yongji Liu, Xiaobi Liu, Shanlan Li, Runping Liu, Bing Xu, Haimin Lei School of Chinese Pharmacy, Beijing University of Chinese Medicine, Beijing, 100102, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haimin Lei, Email hm_lei@126.com Bing Xu, Email weichenxubing@126.comBackground: Sorafenib, a multi-kinase inhibitor, has emerged as a promising therapeutic agent for liver fibrosis due to its ability to target key signaling pathways involved in HSC activation. However, it may inadvertently exacerbate inflammatory responses at certain doses. Recent findings suggest that targeting the STING signaling pathway may provide an alternative strategy for slowing the progression of fibrosis.Methods: We synthesized liver-targeted co-assembled SHG nanoparticles (SHG NPs) that incorporate sorafenib and a hederagenin derivative (Hed), which acted as a STING pathway inhibitor. SHG NPs are preferentially endocytosed by hepatocytes via DSPE-PEG-Gal-mediated ASGPR targeting. After release from hepatocytes, sorafenib diffuses into adjacent HSCs through concentration gradients, effectively inhibiting PDGFR/TGF-β signaling. Hed exhibits dual-targeting characteristics: (1) its STING inhibitory activity selectively acts on macrophage-mediated inflammation; (2) the enhanced phagocytic capacity of Kupffer cells in fibrotic livers promotes non-specific uptake. This spatiotemporal release pattern, combined with pathway-specific pharmacodynamics, ensures synergistic anti-fibrotic effects.Results: In this study, SHG NPs have been successfully formulated with well-defined nanostructures and uniform sizes (115.1 nm). In vitro Sirius Red staining demonstrated that SHG NPs inhibited collagen deposition by 57.5 ± 2.3%, significantly higher than the inhibition observed with sorafenib alone (24.8 ± 1.8%). Furthermore, cell uptake studies confirmed enhanced uptake of SHG NPs in ASGPR-overexpressing cell lines, which was attributed to the presence of galactose on their surface. Additionally, in vivo anti-liver fibrosis activity experiments further confirmed that SHG NPs exhibit superior therapeutic efficacy compared to sorafenib.Conclusion: Our research indicates that formulating sorafenib with a STING pathway inhibitor into liver-targeted nanoparticles represents a potentially effective strategy for the treatment of liver fibrosis. Keywords: liver fibrosis, co-assembly, sorafenib, STING pathway, hederagenin